CBMT-04. MOLECULAR MECHANISM OF OLIG2-CDK2 INTERACTION IN GLIOMA CELLS. (11th November 2019) - Saito, Norihiko; Hirai, Nozomi; Aoki, Kazuya; Sato, Sho; Suzuki, Ryo; Hiramoto, Yu; Nakayama, Haruo; hayashi, Morito; Sakurai, Takatoshi; Iwabuchi, Satoshi
Abstract: Oligodendrocyte transcription factor 2 (OLIG2) promotes proliferation of normal neural stem/progenitor cells and glioma cells. However, the mechanisms underlying the regulation of OLIG2 remain largely unknown. Here we identified OLIG2 as a critical phosphorylation target for cyclin-dependent kinase 2 (CDK2). CDK2-mediated OLIG2 phosphorylation stabilizes OLIG2 protein from proteasomal degradation. Phosphorylated OLIG2 binds to the E-Box regions of p27 promoter and represses p27 transcription, which in turn activates CDK2 in positive feedback manner. CDK2-mediated OLIG2 phosphorylation promotes cell cycle progression, cell proliferation, and tumorigenesis. OLIG2 inhibition disrupted cell cycle control mechanism by decreasing CDK2 and elevating apoptosis-related molecules. Inhibition of CDK2 activity disrupted OLIG2-CDK2 interactions and attenuated OLIG2 protein stability. In addition, OLIG2-high glioma initiating cells are highly sensitive to CDK2 inhibitor treatment, indicating that OLIG2 can be a biomarker for personalized treatment for glioblastoma patients with CDK2 inhibitors. Further investigation on these mechanisms may lead to novel targeted therapy on GBMs with high OLIG2 expression.